Next generation IP network test system framework based on microservices architecture - Jingyi XU; Zeyu ZHAO; Minhu SHEN; ·ibin ·ING; Weiqiang ZHOU (Dianxin kexue)
The next generation IP network is a new type of public network.It integrates wire and wireless,broad-band and narrow-band,transmit and receive,passive and active,which leads to the diverse and complex service scenarios.However,different scenario has different needs and standards,and there remains gaps with the current techniques,protocols and standards.In order to ensure the completeness and security of all kinds of techniques and facilities in the new application scenarios,and the upcoming new characteristics in the process of network development,a comprehensive test system framework needs to be established.The next generation IP network test framework based on micro services architecture was proposed,combined with different new application characteristics,which provided support for the development of network technology.